Panitumumab safety for treating colorectal cancer. (June 2014) - Stremitzer, Stefan; Sebio, Ana; Stintzing, Sebastian; Lenz, Heinz-Josef
Abstract : Introduction: Panitumumab is a human IgG2 mAb against the EGFR, inhibiting tumor cell proliferation, survival and angiogenesis. It has demonstrated clinical efficacy in metastatic colorectal cancer (CRC) in combination with chemotherapy in first- and second-line settings and as monotherapy in third-line setting. Recently, mutations in the RAS genes have been shown to be predictive of lack of efficacy, panitumumab should be restricted to patients with RAS wild-type (wt) tumors. Areas covered: This review focuses on main efficacy results of panitumumab in metastatic CRC in first-, second- and third-line settings in combination with chemotherapy or as monotherapy. Additionally, we have covered safety aspects of this agent in these indications, especially in K-RAS and all RAS wt patients. These safety aspects refer to the most common toxicities (i.e., acne-like skin rash, diarrhea and hypomagnesaemia). Expert opinion: Panitumumab adds to the armamentarium of effective agents in the treatment of metastatic CRC. Due to its human origin, panitumumab is a well-tolerated agent with low rates of infusional reactions. Skin toxicity is frequent and should be pre-emptively treated. Other common toxicities related to panitumumab treatment, such as diarrhea and hypomagnesaemia, should be closely monitored to ensure early treatment or substitution.